PENGEMBANGAN MODEL BAHAN AJAR BAHASA INGGRIS UNTUK PROGRAM EKSTRAKURIKULER DI SEKOLAH DASAR - Pujiati, Hanip; Aisah, Aisah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2015)
Abstract: The objective of this research was to develop a English learning material model for an Extracurricular Program in Elementary Schools. A Research and Development methodology was used involving the following steps: analyzing students’ and teachers’ needs, evaluating the existing learning materials, designing a new learning materials, validating the learning materials by experts, revising learning materials, trying out the learning materials, and revising learning materials. It was found that the existing learning materials were not appropriate for the students’ characteristics and were not organised in a systematic way. Students and teachers indicated that they appreciated enjoyable English language learning materials such as songs, stories and games. Based on these findings a new model for developing materials was developed for Extracurricular English Program in Elementary Schools.